05 Semantic Features (Polisemi, Homonymy) In The Law Terminology in The Albanian And Greek Languages - Eda SHEHU (Association of Social and Educational Innovation, 2015)
Aspects of semantic features in the Albanian lexicon, and in particular the aspects of polysemantics and homo-semantics have been the scope of studies either in isolation or in interaction with one another, but as well they have been studies in relation to many other phenomena such as: the root of the meaning (Thomai,2009), synonymy (Islamaj, 1985) etc. A study of these two phenomena which are closely inter-related is both of theoretical and practical value. In particular, the practical value is directly related to the compilation of explanatory and translation dictionaries (Thomai, 1972), which serves as an interface of the semantic structures of words.